2021
DOI: 10.3390/su13179848
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Use of Water Treatment Sludge in Geotechnical Applications as a Sustainable Alternative to Preserve Natural Soils

Abstract: This paper explores the feasibility of employing drinking water treatment sludge (WTS) mixed with soils, lime, or rock powder in geotechnical applications, as well as discusses the sustainability of the approach based on experimental results, aiming at the beneficial reuse of waste and the preservation of natural geomaterials. The selected materials were two soils largely used in earthworks, two WTSs, a high purity calcium hydrated lime, and rock powder from a granitic–gneissic quarry, all occurring in São Pau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…However, as the sludge content increased to 20%, the MDD value was 2.77% less, and the optimum moisture content OMC% value was 4% higher than those for the samples with 0% sludge. Many earlier studies, like those by [24], had shown that when the sludge content increased, the MDD decreased, and the OMC increased. Due to the strong capacity of sludge to absorb more water required for hydration, the OMC increased when sludge concentration increased.…”
Section: Test Methodsmentioning
confidence: 81%
“…However, as the sludge content increased to 20%, the MDD value was 2.77% less, and the optimum moisture content OMC% value was 4% higher than those for the samples with 0% sludge. Many earlier studies, like those by [24], had shown that when the sludge content increased, the MDD decreased, and the OMC increased. Due to the strong capacity of sludge to absorb more water required for hydration, the OMC increased when sludge concentration increased.…”
Section: Test Methodsmentioning
confidence: 81%
“…Balkaya [15] indicates that in the area of soil enhancement, it emerges as a promising additive that can effectively improve soil quality. This extends to geotechnical applications, as indicated in the article published by Boscov et al [16] in which it stands out as a sustainable alternative to preserve natural soils. Sabo, A et al [17] indicate that the absence of excessive toxic metals in DWTSs, supply of abundant plant nutrients, and lack of harmful toxic metals, emphasizes its viability as a valuable resource for enriching soil nutrients during the reclamation of degraded lands.…”
Section: Introductionmentioning
confidence: 78%
“…The result of organic matter is consistent with previous studies. Ackah et al [22] obtained 34.19% of organic matter in the WTS used in their research, while Boscov et al [35] also obtained high results for organic matter in WTS, with 26.7%. Typically, higher organic content is found in surface water sources [61].…”
Section: Soil and Wtps Characteristicsmentioning
confidence: 83%
“…The Brazilian standard NBR 10004 [51] establishes reference concentrations (QRVs) for chemical elements for leachates and solubilized residues. These extracts generally have lower concentrations than those identified in a sample of gross mass, as evidenced in the studies by Ackah et al [22] and Boscov et al [35]. As described in Annex C of standard NBR 10004 [51], the presence of barium, lead, and chromium in the WTS sample suggests potential toxicity.…”
Section: Soil and Wtps Characteristicsmentioning
confidence: 92%